Effect of Magnetic Field on Electric and Acoustic Properties of the PDMS Ferromagnetic Gel - KUBISZ, Leszek; SKUMIEL, Andrzej; JÓZEFCZAK, Arkadiusz; PANKOWSKI, Edward (Archives of Acoustics, 2008)
A polymer gel (ferrogel) is an assembly of ferromagnetic nanoparticles embeded in gel. In the ferrogel, the finely distributed magnetic particles are suspended in the swelling liquid and forma flexible matrix due to adhesive forces. The present paper describes an electric and acoustic study of magnetic field sensitive poly (dimethyl siloxane) ferrogel. The results showed hysteresis of acoustic properties of the polymer gel due to variation of magnetic field. Electrical measurements showed that electric properties of ferrogel are also affected by magnetic field.